The importance of Guanxi in business in China - Grainger, Stephen (Henry Stewart Talks, 2013)
Defining Guanxi, Business implications, Using Guanxi successfully, China, Mianzi (face), Negotiation, Guanxi base, Guanxiwang, Producing Guanxi, Commitment, Renqing, Transferability, Trust, Real world examples supporting theory and content
Updated at 2014/06/10